Endothelial NOS (NOS3) impairs myocardial function in developing sepsis - van de Sandt, Annette M. (Springer-Verlag, 2013)
Endothelial nitric oxide synthase (NOS)3-derived nitric oxide (NO) modulates inotropic response and diastolic interval for optimal cardiac performance under non-inflammatory conditions. In sepsis, excessive NO production plays a key role in severe hypotension and myocardial dysfunction. We aimed to determine the role of NOS3 on myocardial performance, NO production, and time course of sepsis development. NOS3(−/−) and C57BL/6 wildtype mice were rendered septic by cecum ligation and puncture (CLP). Cardiac function was analyzed by serial echocardiography, in vivo pressure and isolated heart measurements. Cardiac output (CO) increased to 160 % of baseline at 10 h after sepsis induction followed by a decline to 63 % of baseline after 18 h in wildtype mice. CO was unaltered in septic NOS3(−/−) mice. Despite the hyperdynamic state, cardiac function and mean arterial pressure were impaired in septic wildtype as early as 6 h post CLP. At 12 h, cardiac function in septic wildtype was refractory to catecholamines in vivo and respective isolated hearts showed impaired pressure development and limited coronary flow reserve. Hemodynamics remained stable in NOS3(−/−) mice leading to significant survival benefit. Unselective NOS inhibition in septic NOS3(−/−) mice diminished this survival benefit. Plasma NO(x)- and local myocardial NO(x)- and NO levels (via NO spin trapping) demonstrated enhanced NO(x)- and bioactive NO levels in septic wildtype as compared to NOS3(−/−) mice. Significant contribution by inducible NOS (NOS2) during this early phase of sepsis was excluded. Our data suggest that NOS3 relevantly contributes to bioactive NO pool in developing sepsis resulting in impaired cardiac contractility. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00395-013-0330-8) contains supplementary material, which is available to authorized users.